Nuclear-physical methods of analysis of noble metals and rare-earth elements - Dikiy, N.P.; Borovlev, V.I.; Zabolotny, V.D.; Lyashko, Yu.V.; Medvedeva, Y.P.; Slabospitsky, R.P.; Fedorets, I.D.; Shlyakhov, N.A. (Вопросы атомной науки и техники, 2001)
A summary of the analysis noble and rare metals by combined methods is presented. The electrodeposition of gold at a carbon film and Rutherford backscattering was used for determination its in ores. The sorbents and particle induced X-ray emission was used for determination rare and noble metals in ores. The minimum detectable concentration for ores was 0.1 mg/g.